Investigation of five different low-cost locally available isolation layer materials used in sliding base isolation systems. Issue 154 (March 2022) - Ali, Amir; Zhang, Chunwei; Bibi, Tayyaba; Zhu, Limeng; Cao, Liyuan; Li, Chunxiang; Hsiao, Po-Chien
Abstract: The isolation systems based on sliding friction have gained the attention of researchers recently due to their low cost and high efficiency. The isolation layer plays a vital role in the energy dissipation and enhancement of the seismic capacity of an isolation system and is one of the crucial components of the friction-based isolator, thus needs to be designed carefully. Therefore, in this study, five different low-cost and locally available materials were utilized to fabricate the isolation layer and studied analytically, experimentally, and verified numerically. The isolation system under study consists of a low-lateral stiffness material with specific thickness, placed on the surface of low friction Teflon sheet having 3 mm thickness and is sandwiched between the superstructure and foundation. Furthermore, vertical rebars were distributed throughout the isolation layer to ensure the re-centering process. The cyclic behavior of all isolation layer materials was studied by conducting cyclic loading tests, for which the proposed isolation layer materials were sandwiched between two hollow concrete blocks. As friction is the primary source of energy dissipation, so standardized testing methodology was adopted to find the friction among the sliding interface. A detailed analytical study and modal analysis were conducted to identify the response of fixed and isolated models and some important parameters such as fundamental time-period, frequencies, and mode shapes. Based on the experimental study, the rubberized mortar among the others was found as a feasible material for the isolation layer. Later on, a detailed numerical study was conducted in Abaqus by creating a fixed-base and isolated models, whose dynamic behavior was studied under multiple seismic excitations. From the numerical study, the acceleration response reduction of 40%–53% was noticed at the top floor level of an isolated model as compared to the fixed-based model. The low cost and higher effectiveness of the proposed isolation system make it more robust to be used for low-rise masonry structures in developing countries. Highlights: The influence of isolation layer materials on the seismic behavior of the sliding-based isolation system is investigated. Cyclic loading tests were conducted to identify the dynamic response of the isolated model and materials used in the layer. A low-cost isolation system is developed from locally available materials. The proposed friction-based isolation system has a proper re-centering mechanism. A detailed analytical study and numerical verifies the effectiveness of the isolation system.